2009
DOI: 10.1159/000198252
|View full text |Cite
|
Sign up to set email alerts
|

High Flow Insufflation for the Maintenance of the Pneumoperitoneum during Bariatric Surgery

Abstract: Minimally invasive bariatric procedures next to becoming more and more popular have established a new field of applications for carbon dioxide (CO2) insufflators. In laparoscopic bariatric procedures, gas isused toinsufflate the peritoneal cavity and increase the intra-abdominal pressure up to 15 mm Hg for optima lexposure and a suitable operating field. The increased intra-abdominal pressure during pneumoperitoneum can reduce femoral venous flow, intra-operative urine output, portal venous flow, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…The reason that lower intra‐abdominal pressure was not achieved may relate to the limitations of the conventional insufflator device, which uses a low flow carbon dioxide delivery system (e.g. 5 l.min −1 through a Varies needle to 10 l.min −1 through a 5 mm trocar) . When the surgeon uses suction to evacuate smoke or fluids from the abdominal cavity, the pneumoperitoneum will collapse if the suction volume exceeds the pneumoperitoneum volume and the capacity of the insufflator to introduce fresh gas.…”
Section: Discussionmentioning
confidence: 99%
“…The reason that lower intra‐abdominal pressure was not achieved may relate to the limitations of the conventional insufflator device, which uses a low flow carbon dioxide delivery system (e.g. 5 l.min −1 through a Varies needle to 10 l.min −1 through a 5 mm trocar) . When the surgeon uses suction to evacuate smoke or fluids from the abdominal cavity, the pneumoperitoneum will collapse if the suction volume exceeds the pneumoperitoneum volume and the capacity of the insufflator to introduce fresh gas.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous investigation reported that this effect is statistically significant at 10 mmHg, and was maximal at 15 mmHg (12), yet increased pressures do not yield an increased effect, at least in vitro (12). Since the effect is maximal at 15 mmHg and as 15 mmHg is the pressure most commonly used to inflate the abdomen in laparoscopic surgery (13), 15 mmHg was selected to investigate increased pressures above ambient in the present study.…”
Section: Introductionmentioning
confidence: 93%
“…15 Moreover, high thoracic pressure during the operation may decrease pulmonary venous flow, cardiac output, and respiratory compliance, as well as possibly inducing acid-base imbalance due to hypercarbia. 16 On the other hand, gasless methods do not carry the risk of complications such as hypercapnia, respiratory acidosis, tachycardia, subcutaneous emphysema, and air embolism which are present in gas insufflation approaches. 17 Therefore, robotic thyroidectomy is evolving from a gas inflation technique to a gasless technique.…”
Section: Discussionmentioning
confidence: 99%